Mpox transmitted through sexual intercourse: three case reports - Arze, Wilma Nancy Campos; Silva, Ingrid Antunes da; Andrade, Hugo Boechat; Goulart, Aline Gissele Azevedo Ferreira; Goulart Filho, Rubem de Avelar; Morais, Julia Sampaio de Souza; Passos, Carolina Varella Leal; Passos, Paula Varella Leal; Uzeda, Maria Cláudia Pinheiro Guedes de; Bittar, Christina Thereza Machado; Cirne-Santos, Claudio Cesar; Paixão, Izabel Christina Nunes de Palmer; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: In 2022, many countries, such as Brazil, experienced outbreaks of mpox (formerly called monkeypox) in sexually active people with multiple sexual partners. Objective: Report cases of patients diagnosed with Mpox. Methods: Report three cases of patients diagnosed with Mpox treated at the STD Sector at Universidade Federal Fluminense. Results: We report three cases of young adult patients who spontaneously sought our STD service with wounds in the anogenital area, mouth and other parts of the body. These cases include a 28-year-old man (HIV positive) who had lesions on his penis and body, a 34-year-old man with perianal ulcers and adenopathy, and a 40-year-old man with painful ulcers on his penis. Conclusion: The article provides information on the symptoms, transmission, and prevention of mpox, highlighting the need for early detection, diagnosis, and prompt treatment to contain and prevent the spread of the disease. The cases presented in this study show all the characteristics of a sexually transmitted disease.